Artificial intelligence for quality assurance in higher education: a policy-to-practice model from Qatar with global relevance - Rima J. Isaifan (8350056) (2025)
Artificial intelligence (AI) is reshaping the landscape of higher education by redefining how quality is monitored, assured, and enhanced. This paper examines Qatar’s pioneering approach to embedding AI within its national quality assurance and accreditation framework, led by the National Committee for Qualifications and Academic Accreditation (NCQAA). Anchored in Qatar’s National Vision 2030 and National Artificial Intelligence Strategy, the study illustrates how AI-driven tools can strengthen institutional accountability, streamline accreditation processes, and uphold ethical governance. A structured methodological model is proposed to guide higher education institutions in assessing readiness, developing policy, and integrating AI responsibly. Beyond Qatar, the framework offers transferable insights for countries seeking to harmonise innovation with integrity in their quality assurance systems. By translating national policy into institutional practice, the paper highlights AI’s potential to foster transparency, inclusivity, and data-informed decision-making in the pursuit of academic excellence. Other Information Published in: Quality in Higher Education License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/13538322.2025.2576326